2016
DOI: 10.22159/ijpps.2016v8i11.14466
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Depressant Effect of Ceftriaxone in Forced Swimming Test and in Tail Suspension Test in Mice

Abstract: Objective: Depression is a major psychiatric disorder affecting nearly 350 million people worldwide and imposes a substantial health burden on the society. Ceftriaxone has demonstrated neuroprotective effects in animals. It has also undergone trials as a treatment option for amyotrophic lateral sclerosis. This study was therefore undertaken to evaluate the antidepressant-like effect of ceftriaxone in mice.Methods: Ceftriaxone was administered at three different doses (0.130, 0.195 and 0.260g/kg) to Swiss albin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…CEF treated animals also showed a marked decrement of immobility in the forced swim and tail suspension tests. Even though not statistically significant, a similar trend was noted in novelty-suppressed feeding (Mineur et al, 2007;Borah et al, 2018). A more recent study also showed that the antidepressant effect of CEF was comparable to that of fluoxetine in the tail suspension test in a dose-dependent manner (Borah et al, 2018).…”
Section: Antidepressant Effects Of Cefmentioning
confidence: 70%
“…CEF treated animals also showed a marked decrement of immobility in the forced swim and tail suspension tests. Even though not statistically significant, a similar trend was noted in novelty-suppressed feeding (Mineur et al, 2007;Borah et al, 2018). A more recent study also showed that the antidepressant effect of CEF was comparable to that of fluoxetine in the tail suspension test in a dose-dependent manner (Borah et al, 2018).…”
Section: Antidepressant Effects Of Cefmentioning
confidence: 70%
“…Mouse was viewed as stable when it inactively hung with bar without any endeavors to get away. 23 -26…”
Section: Methodsmentioning
confidence: 99%
“…The rats were then allowed to dry in a pre-washed enclosure (~32°C) before being returned to their cages. The decrease in the duration of immobility is a measure of antidepressant activity [22].…”
Section: Fstmentioning
confidence: 99%